Epistemic Disruptions. Autofiction and Identity Politics in Paul B. Preciado’s Can the Monster Speak? (2020) and Kim de l’Horizon’s Blutbuch (2022) - Bremerich, Stephanie (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2024)
The paper examines contemporary autofictional texts about queer identities in the context of current debates on identity politics. Paul B. Preciado’s Can the Monster Speak? (2020) and Kim de l’Horizons’s Blutbuch (2022) reflect queer identities in the form of transgressive and transitory writing which blurs the boundaries between academic and fictional discourse and ultimately leads to a hybridisation of the narrative. Both texts use autofiction as a means of epistemic disruption, that is as a critical questioning of Western epistemology, especially with regard to academic discourse (Preciado) and cultural memory (de l’Horizon). The ‘I’ of the autofiction becomes the catalyst of an anti-hegemonic knowledge and anti-hegemonic discourse and thus performs a core concern of identity politics in a literary way, namely the claiming of a subject and speaker position in the hegemonic discourse. At the same time, the aporias of identity politics discourses also become clear when looking at both autofictions.